STRATEGI BERTAHAN DALAM 5 SERI KOMIK TINTIN KARYA HERGÃ - , FADIAH GITA GHAISANI; , Dr. Wening Udasmoro, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A comic serial of Tintin entitled Tintin en AmÃ©rique, Les Cigares du Pharaon, Le Lotus Bleu, Le Secret de la Licorne, dan Vol 714 Pour Sidney, that was written by HergÃ© in 1929, becomes the object of the material in this thesis. The whole of the story in Tintin the comic tells the readers about an adventure story of a young man in solving international problem through its main character, Tintin. Arrogance of power and threat had to be coped through several ways. Therefore, the writer expresses the characterâs struggle to fight arrogance of power and threat that exists in the story. The writer used strategy and tactic concept written by Michel de Certeau to explain the effort that had been done to survive. The research was started from the explanation of strategy forms that become the fundamental basis of his struggle to fight arrogance of power and threat in solving international problem. Based on the research done, the writer also found several forms of tactic to keep survive as the supporting strategy in defending himself i.e. doerâs modofication tactic, redemption tactic, symbolic tactic, and raid tactic. The forms of those tactic become the solution to achive the characterâs happiness.